Correlations between Information Science research groups in Brazil: an approach based on keywords - Schlogl, Gisele de Felippe; Lima Dutra, Moisés (AWARI, 2020)
Analyzing correlations between research groups has been increasingly appealing in recent years. The identification of proximity between different research projects can not only contribute to triggering new partnerships, but also optimize resources and share results. In Brazil, the Lattes Curriculum System of the Brazilian National Council for Scientific and Technological Development is a rich source of information about the academic and professional life of professors, researchers, and students. Lattes curricula present information, much of it up-to-date, in a semi-structured text format. This paper intends to identify correlations between Brazilian research groups in Information Science through the analysis of keywords contained in the informative summaries and in the descriptions of the research projects found in the Lattes curricula of the participants of these groups. The analysis presented below was made with the application of text mining techniques to the Lattes curricula of researchers linked to 27 graduate programs in Information Science from 24 Brazilian institutions of higher education, totaling 399 curricula analyzed. Among the results obtained, it was possible to identify some existing research trends between the groups and link them to the areas of Information Science, Archivology, Library Science, and Museology. It was also possible to identify the most used research terms at the moment. In addition, the analysis of the occurrence of the terms allowed to identify the areas that concentrate most of the research in Information Science in Brazil, as well as to realize that there is a propensity of researchers to use certain terms to describe their research and their informative summaries.